Sphingosine 1-phosphate, a potential target in neovascular retinal disease. Issue 9 (7th May 2021) - Alshaikh, Rasha A; Ryan, Katie B; Waeber, Christian
Abstract : Neovascular ocular diseases (such as age-related macular degeneration, diabetic retinopathy and retinal vein occlusion) are characterised by common pathological processes that contribute to disease progression. These include angiogenesis, oedema, inflammation, cell death and fibrosis. Currently available therapies target the effects of vascular endothelial growth factor (VEGF), the main mediator of pathological angiogenesis. Unfortunately, VEGF blockers are expensive biological therapeutics that necessitate frequent intravitreal administration and are associated with multiple adverse effects. Thus, alternative treatment options associated with fewer side effects are required for disease management. This review introduces sphingosine 1-phosphate (S1P) as a potential pharmacological target for the treatment of neovascular ocular pathologies. S1P is a sphingolipid mediator that controls cellular growth, differentiation, survival and death. S1P actions are mediated by five G protein-coupled receptors (S1P1–5 receptors) which are abundantly expressed in all retinal and subretinal structures. The action of S1P on S1P1 receptors can reduce angiogenesis, increase endothelium integrity, reduce photoreceptor apoptosis and protect the retina against neurodegeneration. Conversely, S1P2 receptor signalling can increase neovascularisation, disrupt endothelial junctions, stimulate VEGF release, and induce retinal cell apoptosis and degeneration of neural retina. The aim of this review is to thoroughly discuss the role of S1P and its different receptor subtypes in angiogenesis, inflammation, apoptosis and fibrosis in order to determine which of these S1P-mediated processes may be targeted therapeutically.